(untitled) (Hoboken, N.J., 2010)
A Textbook of Modern Toxicology is a unique resource that provides both students and practitioners with a wide-ranging, accessible overview of the discipline. Suitable for courses in environmental, pharmacological, medical, and veterinary toxicology, this essential text features chapters written by experts who address a range of key topics. The Fourth Edition includes additional chapters on new approaches to toxicology - molecular methods (-omics: toxicogenomics, proteomics, and metabolomics), bioinformatics, and systems biology – and continues the legacy of its predecessors to provide up-to-date insights into acute toxicity and chemical carcinogenesis, organ toxicity, in vitro and in vivo toxicity testing, ecological risk assessment, and many other areas of toxicology that help foster a solid comprehension of the field.
Keywords: Độc chất học,Toxicology